Examining the link between research and teaching in UiTM / Kamisah Ariffin and Nazirah Ramli - Ariffin, Kamisah; Ramli, Nazirah (2007)
It has been a widespread view that research and teaching are inextricable linked. Justification on this link has been made based on the ascription that research has beneficial impacts on the process of teaching and learning. However, this paper has illustrated that such claim has been broadly made and not at all conclusive. The analysis on the research carried out by the academics in Universiti Teknologi MARA (UiTM) Pahang shows that there are three possible links between research and teaching: positive or complementary, negative or conflicting, and zero or null. This suggests that the interaction between research and teaching needs to be evaluated and reasoned so that academics would be able to consider the link before undertaking any research activity so as to make the research valuable and meaningful for the teaching and learning processes.